Pengaruh Kemampuan Siswa Dalam Memuraja’ah Hafalan Al-Qur’an di SDIT Baiturrahim Parik Putuih, Kabupaten Agam - S, Selvi; Husni, Arman; Aprison, Wedra; M, Iswantir (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was motivated by the implementation of muraja'ah which was carried out at SDIT Baiturrahim as an effort to increase student memorization. In this activity, students' varying levels of memorization can be seen, so the author is interested in researching the process of implementing muraja'ah to improve student memorization at SDIT Baiturrahim Parik Putuih. The research method that the author carried out in this research was descriptive qualitative research. The data collection process that researchers carried out in this research was through interviews and field observations. The research location is SDIT Baiturrahi m Parik Putuih. The results of this research show that memorization activities have been carried out well at SDIT Baiturrahim Parik Putuih, Agam Regency, this can be seen from the management system implemented by the school which supports increasing student memorization. This can be seen from the majority of class III students who have achieved the target, this is due to motivation, as well as prizes for those who have achieved the target.